Payment Diversion Frauds: An Era of AI-Enabled Cyber Frauds - Shamota, Rahul; Rana, Aditi (Trinity Law Review, 2023)
The era of technology has opened a limitless opportunity of growth for the human society but this limitless opportunities has also opened new doors for the offenders to commit cybercrime at the ease from their home with the use of computers and internet very easily. Lack of time and competitiveness in the market to be the quickest service providers has made the task of verification before making payment by the organization become a very tough and hectic job. And the cyber criminals are using this weak point to attaint their illicit and illmotivated goals very easily. In this article the author has discussed one of the newest kind of fraud that specifically targets the organisations and made them higly vulnerable in the market in relation to their financial activities. The fraud being named as Payment Diversion Fraud because in such kind of fraud the offender did not attract the organization to a fake scheme with lucrative returns but rather make the organization for clearing a payment that is organization required to initiate but the destination of the payment is diverted from the person who is legally authorized to receive the payment to one of the account of the offenders. The author also discussed about the various legal provisions available at international level as well as in India to curb and control cyber frauds that also includes Payment Diversion Frauds. Also at last some suggestion were also provided in which by taking a little extra care and precautions before making a payment the organisations can easily safeguard them from these kind of fraudulent activities.